2021
DOI: 10.3390/polym13244414
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Cd(II) Using a Disposable Optical Sensor Based on a Schiff Base Immobilisation on a Polymer-Inclusion Membrane. Applications in Water and Art Paint Samples

Abstract: A disposable colour-changeable optical sensor based on an interesting polymer inclusion-membrane (PIM) was designed to determine Cd(II) ions in aqueous medium. The Schiff base 2-acetylpyridine benzoylhydrazone (2-APBH) immobilised on the polymer membrane was used as a sensing molecule. The amounts of the PIM components were optimised by a 32 fractional factorial design with two central points and two blocks. The best optical sensor composition consisted of 2.5 g of poly(vinylchloride) (PVC) as a base polymer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…One of the good precursors for the synthesis of potentially biologically active imine derivatives is 2-acetylpyridine. Besides the potential for medicinal application, Schiff bases of this ketone have a wide range of other uses, such as fluorescent and luminescent probes [34,35], optical sensors for determination of cadmium(II) in natural water and art-paint samples [36], effective catalysts [37], etc. The research has shown that imine derivatives of 2-acetylpyridine and their metal complexes express substantial in vitro activity against various human tumor lines [38,39] and significant cytotoxicity against some solid tumors and leukemia cells [40].…”
Section: Significance and Applicationmentioning
confidence: 99%
“…One of the good precursors for the synthesis of potentially biologically active imine derivatives is 2-acetylpyridine. Besides the potential for medicinal application, Schiff bases of this ketone have a wide range of other uses, such as fluorescent and luminescent probes [34,35], optical sensors for determination of cadmium(II) in natural water and art-paint samples [36], effective catalysts [37], etc. The research has shown that imine derivatives of 2-acetylpyridine and their metal complexes express substantial in vitro activity against various human tumor lines [38,39] and significant cytotoxicity against some solid tumors and leukemia cells [40].…”
Section: Significance and Applicationmentioning
confidence: 99%
“…Azomethines (Schiff bases) are promising compounds for use in various fields of science and technology: extraction of metals [1,2], analytical chemistry [3], chemosensorics [4], polymer photostabilization [5], etc. Azomethines inhibit steel corrosion in hydrochloric [6] and sulfuric [7] acid solutions since they are easily adsorbed at the metal/solution interface.…”
Section: Introductionmentioning
confidence: 99%